CARACTÉRISATION MOLÉCULAIRE ET ASSOCIATION MARQUEUR SSR PHÉNOTYPE POUR LA TOLÉRANCE AU STRESS HYDRIQUE CHEZ LE BLÉ DUR (TRITICUM DURUM DESF) - Bousba Ratiba; Djekoun Abdelhamid; Duraa Susan; Ykhlef Nadia (European Scientific Journal, ESJ, 2013)
The objective of this study is to investigate the genotypic differences for several morpho physiological parameters in different water conditions. Twenty varieties of durum local and introduced were grown in pots. Measures of morpho physiological parameters were performed. These measures have focused on the rate of chlorophyll (SPAD unit), the relative water content RWC%, Cell Integrity (%), leaf area (cm2) and stomatal resistance. The results show a significant variability between varieties and between treatments. The distribution follows a normal variation in phenotypic continuous quantitative variation. Data variability morphophysiological were used for association analysis marker / phenotype. The majority of used markers are associated with studied traits under water stress like; WMS135, WMC54, WMC63, WMC165, WMC 150 WMC167, WMS198, WMC177, WMS 6et WMC235; located respectively on chromosomes 1A, 3B, 2A, 3A, 4A, 2A, 2A, 2B, 4B and 5B, which are respectively involved in the variation in the studied characters. These markers could be used for marker-assisted selection in durum wheat breeding under drought conditions , and new strategies could be developed to safeguard and improve our autochthon germoplasm for drought tolerance.